Corrigendum to Compatibility of household appliances with DC microgrid for PV systems [Heliyon 6 (12), (December 2020) Article e05699] (Heliyon (2020) 6(12), (S2405844020325421), (10.1016/j.heliyon.2020.e05699)) - Sabry A.H.; Shallal A.H.; Hameed H.S.; Ker P.J. (Elsevier Ltd, 2023)
In the original published version of this article, the Funding Statement was erroneously recorded as This work was supported by Universiti Tenaga Nasional for the UNIIG fund (Project Code: J510050802). The correct Funding Statement, This work was supported by the Universiti Tenaga Nasional Internal Grant (Project code: RJO10517844/054) and the BOLD Refresh Publication Fund 2021 (J5100D4103) has now been recorded. The authors apologize for the errors. Both the HTML and PDF versions of the article have been updated to correct the errors. 2020 The Author(s)